Variations of Islam and democracy in Muslim countries: From Islamic countries to secular Muslim countries and its relevance to the discourse of Islam and democracy - Zulfadli Zulfadli (Faculty of Social and Political Science, Universitas Airlangga, 2022)
The phenomenon of Islam and democracy in Muslim countries is practiced differently between Muslim countries with an Islamic state and Muslim countries with a secular pattern. This article wants to examine and reassess the view of Islamic exceptions or “Islamic exceptionalism” on the scarcity of democracy in Muslim countries with case studies of regime variations found in Muslim countries. This article analyzes the variation of Islam and democracy in Muslim countries, with a comparative method using data from the democracy indexing agency. There are four variations of Muslim countries: Islamic countries, semi-Islamic countries, secular countries, and semi-secular countries. This study shows that, from the four variations of the Islamic world, none of the Islamic countries has succeeded in achieving full democracy (full democracy). Three Muslim countries have a flawed democracy (flawed democracy), namely Malaysia, Indonesia, and Tunisia. The rest of the Muslim countries are under a political system controlled by the military (hybrid democracy) and authoritarianism. In addition, this article finds that social, political, cultural, and agency tools and support in supporting democratic values are still the main problems that harm the scarcity of democracy in Muslim societies